Global Value Chains: the Rise (and Fall?) of Deep Globalisation - Kaplinsky , Raphael (Papeles de Europa, 2023)
This paper analyzes the role played by global value chains (GVCs) in the maintenance of the mass production paradigm from the 1980s onwards, relating the decline in the participation of GVCs to the fracture of this paradigm. The second part analyzes the emergence of the new techno-economic paradigm of ICTs, concluding that, although it will not cause the collapse of globalization, it will change its nature. Finance, investment, knowledge, technology and values will continue to spread globally, but production will move increasingly closer to consumption. But cross-border value chains will continue to expand, and will be predominantly regional rather than global.